2014
DOI: 10.1177/070674371405900403
|View full text |Cite
|
Sign up to set email alerts
|

Implementing a Continuum of Evidence-Based Psychosocial Interventions for People with Severe Mental Illness: Part 2—Review of Critical Implementation Issues

Abstract: The issues identified in this review should be taken into consideration by stakeholders when engaging in efforts to promote uptake of new psychosocial EBPs and to widen the range of effective psychosocial services available in routine mental health care.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
55
0
3

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 39 publications
(64 citation statements)
references
References 77 publications
(223 reference statements)
3
55
0
3
Order By: Relevance
“…However, the ministry has not supported training psychiatrists in the new role, nor monitored the implementation of the responding psychiatrists program. A review of the system implementation strategies showed that state technical assistance centres shall be considered [25]. Such centres provide initial training of the innovative program, community of practice monthly discussion, monitoring of quality and accreditation.…”
Section: Maintenance Of the Programmentioning
confidence: 99%
“…However, the ministry has not supported training psychiatrists in the new role, nor monitored the implementation of the responding psychiatrists program. A review of the system implementation strategies showed that state technical assistance centres shall be considered [25]. Such centres provide initial training of the innovative program, community of practice monthly discussion, monitoring of quality and accreditation.…”
Section: Maintenance Of the Programmentioning
confidence: 99%
“…Le domaine de l'application des connaissances et de l'amélioration des pratiques est clair ; l'implantation des meilleures pratiques est facilitée dans un climat organisationnel encourageant les opportunités de formation et de partage de connaissances ainsi que dans un contexte de souplesse et de flexibilité des mécanismes et ressources de soutien (Briand et Menear, 2014). Le manque de financement pour poursuivre le développement professionnel et l'absence d'incitations pour promouvoir des services de haute qualité peuvent saper le moral du personnel et ralentir l'absorption des meilleures pratiques (Amodeo et al, 2011 ;Berry et Haddock, 2008 ;McHugh et Barlow, 2010 ;Thornicroft et al, 2008).…”
Section: Tableauunclassified
“…Assertive early detection teams are important to reduce treatment delays because the rates of absence at appointments for these patients are high and often caused by their symptoms . (ii) Improvement of quality of care to improve outcome: An increase of quality of care can be achieved by the implementation of service structures created for patients with SMI . This comprises, on a structural level, a team‐based model of assertive outreach, early detection service, peer‐to‐peer counselling, support structures for school, education, work, finances and housing and structures for the prevention and treatment of somatic illnesses .…”
Section: Introductionmentioning
confidence: 99%
“…Models of assertive outreach include Assertive Community Treatment (ACT) with its modifications Resource Group ACT (RACT), Therapeutic ACT (TACT) or Flexible ACT (FACT), Crisis Resolution and Home Treatment (CRHT) and Community Mental Health Teams (CMHT) . On the content level, such services should provide integrated care with individualized, evidence‐based and diagnosis‐specific psychological, social and somatic interventions …”
Section: Introductionmentioning
confidence: 99%